Clinical experience with medical hypnosis as an adjunctive therapy in heart surgery - Tigges-Limmer, Katharina; Brocks, Yvonne; Winkler, Yvonne; Stock Gissendanner, Scott; Gummert, Jan (Frontiers in Psychology, 2024)
Heart surgery patients are at high risk for psychological trauma and comorbid psychological disorders. Depression, anxiety, and post-traumatic stress disorders in this patient group are predictors of outcomes after cardiac surgery. Medical hypnosis is effective for non-pharmacologic prevention and treatment of psychological disorders and has been associated with improved health-related quality of life and better cardiovascular outcomes. This contribution makes note of evidence of the effectiveness of medical hypnosis in a discussion of the clinical experience with specific hypnotherapeutic tools and interventions from the perspective of the mental health team in one large cardiac center in Germany. Based on our experience, we encourage heart centers to educate their heart surgery care teams about the core concepts of medical hypnosis and to make hypnotherapeutic techniques available as an adjunctive therapy.